The Position of Diversion Against Victims of Child Sexual Abuse - Kamarmir, Zulfikar; Dame Panjaitan, Junifer (International Journal of Social Research, 2024)
The application of diversity by law enforcement officials is based on the authority of law enforcement officials called discretion or child discretion as the potential of the state in the context of the survival and glory of the nation, is how the government's commitment in making children superior. priority in the formation of juvenile judges and courts as the last bastion in the process of resolving children who face the law in Court. Police and communities must synergize and develop common perceptions of diversion and restorative justice. Parents must participate in providing protection to children by fulfilling children's rights, protecting children's interests and further increasing supervision of children's environments and playgrounds.